Consequências do uso de madeira tratada com CCA e de painéis de MDF como combustível em processos de combustão - Tomeleri, João Otávio Poletto (Universidade Federal de São Carlos, 2019)
From its use for domestic purposes like firewood to the application in large industrial processing plants for power generation, wood is a long-established fuel. Although its application has evolved towards the establishment of new technologies in conversion systems and the development of energy forests, the current context of the need to reuse urban and industrial waste has introduced a new challenge, that of associating the energy utilization of these materials with the volume reduction for landfills. Aiming to evaluate the combustion behavior of six types of lignocellulosic materials, the untreated wood of pine and eucalyptus, pinus and eucalyptus treated with CCA and MDF panels with and without melamine coating were sampled. The treatments underwent elemental analysis, immediate analysis, higher calorific value, thermogravimetric analysis, structural analysis of the ashes by scanning electron microscopy and chemical composition by X-ray spectroscopy. The results showed that, in general, the low moisture content presented by all the materials are the main advantage presented by the residues in relation to the maintenance of the efficiency of the burning processes. However, the materials with the greatest association with non-lignocellulosic elements showed a significantly higher ash yield compared to untreated wood. In addition, the presence of the CCA and the melamine coating were responsible for the alteration of the chemical and morphological composition of these combustion residues, producing partial burning particles containing chromium, copper and arsenic for the treated wood and large melamine particles containing chlorine and titanium for the coated panel. In relation to the higher calorific value, untreated pine wood was the material that presented the best result among all the tested, and the coated panel had the lowest value for this parameter. The variations in the energy parameters do not prevent combustion from being considered as a technologically viable alternative in the reduction of the volume of solid waste wood as well as in the generation of energy. However, the identification of toxic elements in the combustion residues of treated wood demonstrates the need to develop practices to mitigate the risks of environmental pollution that the disposal of the ashes represents.
Consequences of using treated wood and wood panels as fuel in combustion processes
Keywords: Madeira residual; Análise elementar; Análise térmica; Combustão; Waste wood; Elemental analysis; Thermal analysis; Combustion; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::ENERGIA DE BIOMASSA FLORESTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS